The strategic uses of collagen in adherent cell cultures - Pin Fen, Chua; William K., Lim (John Wiley & Sons, Ltd, 2022)
The culture of adherent mammalian cells involves adhesion to the tissue culture vessel. This requires attachment factors from serum and/or a suitable substrate on the vessel surface. Some cells require collagen or other substrates to promote neurite outgrowth, differentiation or growth. However, laboratories often lack guidance on the selection and/or optimisation of collagen. We model such selection/optimisation work in the PC12 neuronal cell line. PC12 (NS-1 variant) cells require a substrate for adherence. Comparing cell attachment against a series of substrates, we found collagen IV to be optimal. We show by comparison of morphology against a range of concentrations that 10 µg/ml is sufficient for supporting cell attachment, and also differentiation. PC12 cells from Riken Cell Bank do not require a substrate for routine culturing but only for differentiation. As all substrates supported attachment equally well, we used a novel serum-free approach and identified collagen IV as its preferred substrate. For these cells, Dulbecco's modified eagle's medium but not Roswell Park Memorial Institute (RPMI) media supports normal cell attachment. However, coating with collagen IV enabled the cells to grow equally well in RPMI. Hence the strategic use of collagen is essential in laboratories working with anchorage-dependent cell lines.